The safety of isotretinoin treatment in patients with bone fractures - Miziołek, Bartosz; Bergler-Czop, Beata; Stańkowska, Anna; Brzezińska-Wcisło, Ligia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2019)
Isotretinoin is widely applicable in dermatology, although it may develop severe side effects in the skeletal system. An intention of this review was to establish the safety of oral isotretinoin in patients with bone fractures. Both MEDLINE/Pubmed and SCOPUS databases were searched to investigate the influence of isotretinoin on the skeletal system. The drug shows a strong osteoporotic activity in rats whereas this effect is milder in humans. Biochemical markers of bone turnover remain unchanged except for serum calcium in patients receiving a high dose of isotretinoin. An excessive intake of vitamin A may impair functioning of vitamin D especially in people with a vitamin D deficiency, therefore a similar side effect may also occur in patients on isotretinoin treatment. We suggest reducing the use of isotretinoin after bone injury or continuing the treatment at low dosing with a concomitant correction of vitamin D and calcium status.